Reoperation for failed shoulder reconstruction following brachial plexus birth injury - Price, Andrew E; Fajardo, Marc; Grossman, John AI (Journal of Brachial Plexus and Peripheral Nerve Injury, 2013)
Background Various approaches have been developed to treat the progressive shoulder deformity in patients with brachial plexus birth palsy. Reconstructive surgery for this condition consists of complex procedures with a risk for failure.Case presentations This is a retrospective case review of the outcome in eight cases referred to us for reoperation for failed shoulder reconstructions. In each case, we describe the initial attempt(s) at surgical correction, the underlying causes of failure, and the procedures performed to rectify the problem. Results were assessed using pre- and post-operative Mallet shoulder scores. All eight patients realized improvement in shoulder function from reoperation.Conclusions This case review identifies several aspects of reconstructive shoulder surgery for brachial plexus birth injury that may cause failure of the index procedure(s) and outlines critical steps in the evaluation and execution of shoulder reconstruction.
Keywords: Brachial plexus birth palsy; Reoperation; Revision surgery; Reconstruction